Effects of scorpion venom heat-resistant peptide on the hippocampal neurons of kainic acid-induced epileptic rats - Chen,Qizuan (2021)
Scorpion venom is a Chinese medicine for epilepsy treatment, but the underlying mechanism is not clear. Scorpion venom heat-resistant peptide (SVHRP), a peptide isolated from the venom of Buthus martensii Karsch, has an anti-epileptic effect by reducing seizure behavior according to a modified Racine scale. The present study aimed to investigate the molecular mechanism of SVHRP on temporal lobe epilepsy. The hippocampus and hippocampal neurons from kainic acid-induced epileptic rats were treated with SVHRP at different doses and duration. Quantitative RT-PCR and immunoblotting were used to detect the expression level of brain-derived neurotrophic factor (BDNF), neuropeptide Y (NPY), cAMP-response element binding protein (CREB), stromal interaction molecule (STIM), and calcium release-activated calcium channel protein 1 (ORAI1). In the hippocampal tissues and primary hippocampal neuron cultures, SVHRP treatment resulted in increased mRNA and protein levels of BDNF and NPY under the epileptic condition. The upregulation of BDNF and NPY expression was positively correlated with the dose level and treatment duration of SVHRP in hippocampal tissues from kainic acid-induced epileptic rats. On the other hand, no significant changes in the levels of CREB, STIM, or ORAI1 were observed. SVHRP may exhibit an anti-epileptic effect by upregulating the expression of BDNF and NPY in the epileptic hippocampus.